PERAN PEMERINTAH DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN DI SEKTOR PERIKANAN : (Studi Pengembangan Pelabuhan Perikanan Pantai Tambakrejo di Blitar) - Ferida Asih Wiludjeng (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2018)
This study aims to determine and explain the role of the government in realizing sustainable development in the fisheries sector in the development of Tambakrejo Beach Fisheries Port in Blitar, as well as the inhibiting factors of the government's role in realizing sustainable development in the fisheries sector. This study uses a qualitative approach type of descriptive research. The source of the data obtained is from informants who are employees of the UPT in the Blitar region. The results of this study indicate that local governments have played a role in providing port facilities, supervision and control of ports to bring order to fishermen who sail and maintain fisheries ecosystems. In the process of development, Tambakrejo Beach Fisheries Port in Blitar Regency has several inhibiting factors, namely the lack of human resources in charge of maintaining and maintaining port buildings, lack of concern for service users towards fishing ports.